Prevalence of preoperative cognitive impairment among elderly thoracic surgery patients and association with postoperative delirium: a prospective observational study - Li, Fangfang; Miao, Mengrong; Li, Ningning; Zhou, Jun; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Human Neuroscience, 2023)
Background Preoperative cognitive impairment (PCI) may increase the incidence of postoperative delirium (POD), yet screening for cognitive impairment is rarely performed. This study hypothesized that Mini-Cog for preoperative cognitive impairment screening predicts postoperative delirium. Methods The prospective observational study recruited 153 elderly patients presenting for elective thoracic surgery. Cognitive function of these patients was screened using Mini-Cog preoperatively. We considered that patients with Mini-Cog scores ≤ 3 had cognitive impairment. Delirium was assessed using the Short CAM scale on postoperative days 1–5. Results Of the 153 participants, 54 (35.3%) were assigned to the PCI group, and 99 (64.7%) were assigned to the Normal group. Place of residence, education level, and history of hypertension were significantly different between the two groups (P < 0.05). 51 (33.3%) patients developed POD. Multifactorial analysis revealed that PCI (OR = 2.37, P = 0.028), older age (OR = 1.13, P = 0.009), ASA grade III (OR = 2.75, P = 0.012), and longer duration of anesthesia (OR = 1.01, P = 0.007) were associated with POD. Conclusion Preoperative cognitive impairment is strongly associated with POD. Mini-Cog could be recommended for screening PCI. Clinical trial registration ClinicalTrials.gov, identifier NCT05798767.